Investigation of the Properties of Nickel Titanium Shape Memory Alloys for Applications in Self-Healing Materials - (:unkn) unknown (My University, 2023)
This research explores the design and properties of self-healing metal-metal composites, with a specific focus on incorporating shape memory alloys (SMAs) and investigating the characteristics of post-constrained recovery residual stresses (PCRRS). The objective is to enhance the functionality, durability, and longevity of mechanical structures through the realization and optimization of self-healing materials. The research delves into the experimental and analytical studies to gain a comprehensive understanding of the underlying mechanisms of PCRRS and SMA-reinforced self-healing metal matrix composites, specifically examining the interface strength between nickel-titanium (NiTi) wire and bismuth-tin (BiSn) solder. NiTi SMAs manifest a distinctive property, termed as PCRRS, observed when they undergo a path of constrained recovery and are subsequently brought back to a low-temperature state while being constrained. This research pursued an array of mechanical experiments to delve deeper into the nature of the PCRRS state. Principal tasks encompassed evaluating the stability of PCRRS across various cycles involving different strain applications, discerning the impact of pre-working or training on PCRRS, studying the mechanical properties while loading from the PCRRS state, analyzing the material phase in the PCRRS state, and assessing the regeneration capabilities of the PCRRS in NiTi SMAs. This research showcases the stability and repeatability of PCRRS, thereby offering invaluable insights into its prospective application in self-healing mechanisms, underscored by its ability to actuate without the continuous provision of energy. Moreover, this thesis elucidates the interfacial attributes between NiTi and BiSn, considering the complications posed by the development of an inert titanium dioxide (TiO2) layer on NiTi. As interfacial bonding is crucial for composite behavior, experimental and theoretical approaches were employed to understand the interfacial bonding, by studying the pull-out behavior of NiTi wires embedded in the BiSn matrix. In this investigation, two different states of NiTi wire were examined in a comparative study – one state maintained the presence of the TiO2 layer as a control, while the other state represented an experimental condition where the TiO2 layer was removed through a chemical etching procedure carried out in an inert environment. Subsequent to testing, the specimens undergo a microscopic assessment to identify the failure modes at the interface. The study reveals the influence of interfacial strength on the pull-out process and highlights the presence of an alternative failure mechanism involving mechanical interlocking. This study's results will quantify the enhanced NiTi and BiSn interfacial strength from the applied process, providing vital data for optimizing composite design and performance. The findings of this research contribute to the understanding of self-healing materials and their potential in engineering applications. Characterization of PCRRS of NiTi SMAs and the interfacial characteristics of NiTi and BiSn, broadly metal-metal self-healing composite offer new possibilities for designing structures with enhanced durability, reduced maintenance requirements, and the ability to restore functionality after damage. These insights provide a foundation for further advancements in the field of self-healing materials and their practical implementation in real-world engineering scenarios.
Keywords: Interfacial Bonding; Metal-Metal Composite (MMC); Nickel Titanium (NiTi); Post-Constrained Recovery Residual Stress (PCRRS); Self-Healing Materials; Shape Memory Alloy (SMA)